Prioritisation in Haemophilia A: A Qualitative Study of Stakeholder Attitudes and Preferences - Dörries, A.; Ude-Koeller, S.; Wermes, C.; Eisert, R.; Ganser, A. (Klinische Pädiatrie, 2012)
To learn more about prioritisation in the health care system, we performed an exploratory qualitative study on haemophilia A. The aim was to generate haemophilia disease-specific criteria and to learn more about reasoning in the decision-making process. The 40 participants (patients, relatives, physicians, nurses) were asked in semi-structured interviews about their experiences regarding the German health care system in general and the management of haemophilia A. The 4 stakeholder groups agreed that treatment in haemophilia A was very good; there were complaints about increased bureaucracy. Arguments originated in personal past experiences (patients, relatives) and in the professional background (healthcare professionals). Decision-making criteria ranking high were the maintenance of mobility, social responsibility and the prospect of a long working life span. Criteria with lower ranking were a high social professional status and age. There was ambivalence as to whether savings in the healthcare system in general were necessary or inacceptable. Prophylactic factor administration was rejected when high-risk sports were practiced regularly. Decision-making among actual individuals was rejected as ‘immoral’. Patient representatives should be included in the political decision-making process. In conclusion, solidarity in the German health insurance is a highly esteemed principle, but was not well comprehended. The findings demonstrate the variety of individual attitudes with strong context affinity to the disease and the background of the stakeholder groups. The challenge will be to find ways of prioritising in an accountable and transparent way to maintain an excellent health care service for the individual haemophilia patient while also serving the public good.
Keywords: priority setting; resource allocation; prioritisation; qualitative study; haemophilia A